Counter effects of Asiaticosids-D through putative neurotransmission on rotenone induced cerebral ganglionic injury in Lumbricus terrestris. (June 2019) - Subaraja, Mamangam; Vanisree, Arambakkam Janardhanam
Highlights: Asiaticoside –D (AD) impact of ganglioside in cerebral ganglions (CGs) of rotenone (ROT)- induced Lumbricus terestris . Effects of AD on variations of mRNA and protein in CGs of ROT- induced. AD could maintain the neuroinflammation of ganglionic degenerative worms. Abstract: Asiaticoside-D (AD) was shown to efficacy of ganglionic degenerated Lumbricus terrestris as a pioneering observation in our earlier research. Though, extract molecular mechanisms of AD for degenerative diseases (DDs) remains largely unknown. We investigated the neuroprotective effects of AD against ROT in cerebral ganglions (CGs) of degenerative L. terrestris . Worms were exposed to 0.4 ppm ROT for 7 days were subjected to co- treatment with 15 ppm of AD. After, CGs was removed. The levels oxidant, non-antioxidant, antioxidant status, ganglioside, ceramide and ceramide glycanase (CGase) were estimated. The m-RNA levels of dopamine transporter ( DAT), octopamine transporter (OAT), innexin s-9 (inx-9), ionotropic glutamate receptor 3 (iGlu3), heat shock proteins (hs p70 ), XPRLamide neuropeptide precursor, tyramine beta-hydroxylase (tbh-1) and β- adrenergic receptor kinase-2 (β-ARK2–3) by semi-qRT- PCR. The expression pattern of tyramine beta hydroxylase (TBH), glutamate receptor (iGluR), serotonin transporter (SERT), dopamine transporters (DAT), nerve growth factors (NGF), cytochrome C oxidase (COC), NADH dehydogenase subunit-1 (ND-1), neurotrophin receptor p75 (p75NTR), neuronal nitric oxiside synthase (nNOs) interleukin 1- beta (IL1-β) and tumor necrosis factor alpha (TNF-α) by western blotting. Glutaminergic, serotogenic and dopaminergic toxicity variations were also performed. The levels of oxidant, non-antioxidant, antioxidant status, lipids, proteins and m-RNAs were significantly altered ( p < 0.001) on ROT-induced (group II) and their levels were significantly changes ( p < 0.05) by ROT+AD in CGs. The sensitive study plan concluded the neuroprotective effects of AD against ROT induced degeneration in worms and suggest that the AD deserves future studies for its use as an effective alternative medicine that could minimize the morbidity of ganglionic degenerative diseases patients.